The Effectiveness of Subintimal Balloon Angioplasty in the Treatment of Critical Lower Limb Ischemia in Patients with Diabetes Mellitus - Sattarov I.S; Matmurotov K.Zh; Yakubov I.Y; Rakhimov D.J (Zien Journals, 2023)
The aim of the study is to present the immediate and long-term results of treatment of patients with diabetic foot syndrome using subintimal balloon angioplasty.
Keywords: diabetes mellitus; diabetic foot syndrome; subintimal balloon angioplasty